ChemInform Abstract: Catalyst‐Free Three‐Component Domino Reactions for Regioselective Synthesis of Multi‐Functional Fused Pyrroles. Issue 41 (October 2015) - Chen, Xue‐Bing; Yan, Sheng‐Jiao; Su, An; Liu, Wei; Lin, Jun
Abstract Starting from heterocyclic ketene aminals, arylglyoxal monohydrates and 1, 3‐diphenylpropane‐1, 3‐dione an efficient domino [3 + 2]‐cyclization is developed which provides fused pyrrole derivatives in high yields and with excellent regioselectivity.